MIAROLITIC MINERALS FROM THE MALY KUYBAS MAGNETITE SKARN DEPOSIT - S.G. Epanchintsev; V.A. Popov (Минералогия)
The Maly Kuybas magnetite skarn deposit is located in the Magnitogorsk mining district (Southern Urals) 15–18 km northeast from the town of Magnitogorsk. The exploitation of the deposit began in the 1970s and the open pit is currently exploited. Only brief data on mineralogy of the deposit are known in literature. This paper provides more complete description of skarn mineralization, which implies the technological properties of ores.